“Be Worried, be VERY Worried:” Preferences for and Impacts of Negative Emotional Climate Change Communication - Bloodhart, Brittany; Swim, Janet K.; Dicicco, Elaine (Frontiers in Communication, 2019)
While communication experts largely recommend avoiding climate change messages that create negative emotional states, little is known regarding how members of the public use emotions in their own communication about climate change. Given the important role individuals can play in addressing climate change via their interpersonal communication, it is important to understand preferences for using or avoiding communication framed with negative emotions, and their ultimate impact on taking action to address climate change. Further, social expectations about the use of emotions may influence whether individuals’ gender and political identity impacts their preference for using specific types of emotions. Three studies tested preferences for and impacts of three negative emotions common to climate change responses: fear, sadness, and anger, in comparison to messages framed without emotion. Findings indicate that people generally prefer messages framed without emotion, although in line with predictions, women and Democrats are more apt to prefer emotional messages than men and Republicans. Although participants say they prefer messages framed without emotion, climate change messages framed with negative emotions are more likely than messages framed without emotion to match participants’ feelings on climate change, while messages framed with specific types of negative emotions are more likely than messages framed without emotion to convey impressions of the speaker as rational, strong, and caring, which in turn predict greater preference for emotional over non-emotional messages. Further, results from a petition-signing study indicate that communicating with negative emotions does not promote nor hinder behavioral engagement.